The influence of electronic exposure and heat treatment on the electroconductivity of epoxypolymer materials - Udovytska, Yuliia; Luniov, Sergiy; Kashytskyi, Vitalii; Maslyuk, Volodymyr; Megela, Ivan (Technical Sciences, 2020)
The influence of electron irradiation fluxes with energy of 12 MeV and heat treatment on the electrical properties of epoxypolymers with PEPA content of 11, 12 and 13 wt.h. per 100 wt. including epoxy resin. It is show that the electrical conductivity of epoxypolymer increases with electron irradiation fluxes greater than 10 kGy. It found that extra heat treatment of irradiated samples with a hardener content of 12 wt. h. hours leads to an increase in their electrical conductivity. The nature of the obtained dependences of electrical conductivity is determine by the processes of cross-linking, radiation, thermal destruction and mass fraction of the hardener. Radiation-stimulated increase in the conductivity of epoxypolymers can be use to create conductive protective coatings and sensor electronics elements